The Cooperative Script Method in Improving Students' Understanding in The Muthala'ah Subject at SMP Galih Agung - Nurainun Hasibuan; Dea Pramesty Cahyani; Naqibah Mansor (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
This study aims to improve students' understanding of Mutala'ah, with a specific focus on the topic of Al-Babga', through the application of the Cooperative Script learning model. This study was conducted using a classroom action research design, which was carried out in two cycles, each consisting of four phases: planning, implementation, observation, and reflection. This study involved 24 students from class II-A at Galih Agung Private Junior High School, Darularafah Raya Islamic Boarding School. Data collection was carried out using learning outcome tests to measure understanding and activity observation sheets to assess student engagement and participation during the learning process. The results showed a significant increase in students' understanding of the material. At the beginning of the study, the average student score was 51.4, and only 42% of students met the minimum mastery criteria. After the implementation of the first cycle, the average score increased to 59.5, with 67% of students achieving mastery. In the second cycle, the average score increased significantly to 75.2, while the proportion of students who achieved mastery increased to 92%. These results show that the Cooperative Script Model is very effective in improving students' understanding of Mutala'ah material. In addition to improving learning outcomes, the use of the Cooperative Script approach also encourages active student participation and promotes collaboration.